Ecopoiesis and econoesis of Okam’s Difu - WALIYA, Yohanna Joseph (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2022)
Ecocriticism is a reaction to the increase in environmental consciousness. It is a kind of literary criticism that focuses on how literary writings contribute to ecology. Ecological theory is used to examine the interaction between the biological environment and the text. It looks at the aesthetics of literature and the philosophical connections between people, the environment, and texts. This article within the domain of ecocriticism aims at analysing Okam’s writing style as it interplays with the propensity of Ameshi villagers in Difu to confirm the people’s raison d’être. However, Hubert Zapf’s theory of imaginative literature is employed to interpret the nature of cultural interconnectedness and diversity in the masterpiece under the aegis of the hypothetico-deductive method and the literary cultural-ecological approach. These methodologies imply that new hypotheses are derived from spontaneous relational conversations between the characters in the drama and their environment, which serve as reservoirs of cultural-ecological knowledge. This study begins with a discussion of ecocriticism in literature, followed by a description of the theory of creative literature to expand on Hubert Zapf’s ideas and confirm results from evaluating the playwright’s ecopoiesis and characters’ econoesis in certain extracted samples of Difu. Finally, it shows the interconnectedness of nature in the play vis-à-vis Ameshi’s culture.